2017
DOI: 10.1128/jcm.02020-16
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Strain Comparison between Hepatitis E Viruses in Human Sera and Pig Livers during 2014 to 2016 in Hong Kong

Abstract: Hepatitis E virus (HEV) causes substantial morbidity and mortality in developing countries and is considered an emerging foodborne pathogen in developed countries in which it was previously not endemic. To investigate genetic association between human HEV infection and HEV-contaminated high-risk food in Hong Kong, we compared local virus strains obtained from hepatitis E patient sera with those surveyed from high-risk food items during 2014 to 2016. Twenty-four cases of laboratory-confirmed human HEV infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
1
14
1
Order By: Relevance
“…As the genotype 3 virus detected in the majority of our human samples infects animals and is known to transmit to humans through the ingestion of contaminated food products like those derived from pigs, shellfish, deer and wild boars (Crossan et al, ; Spancerniene et al, ), it is noteworthy that we found HEV in a food source in Singapore that could be a potential contributor to autochthonous infection and could account for the observed rise in endemicity of hepatitis E. Although the human serum and pig liver samples were not contemporaneously collected, the discovery of genetically similar HEV genotype 3a strains in both of them raises the possibility of an association between HEV infection in Singapore and the consumption of pork and pig products. The sequence similarity of the porcine strains to human strains was high, with the highest nucleotide identity (98.5%) reported here being similar to those reported in other countries like France (96.7%) (Colson et al, ) and Hong Kong (97.8%) (Chan et al, ). The association is further supported by our finding of disproportionate representation of HEV infections by ethnicity.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…As the genotype 3 virus detected in the majority of our human samples infects animals and is known to transmit to humans through the ingestion of contaminated food products like those derived from pigs, shellfish, deer and wild boars (Crossan et al, ; Spancerniene et al, ), it is noteworthy that we found HEV in a food source in Singapore that could be a potential contributor to autochthonous infection and could account for the observed rise in endemicity of hepatitis E. Although the human serum and pig liver samples were not contemporaneously collected, the discovery of genetically similar HEV genotype 3a strains in both of them raises the possibility of an association between HEV infection in Singapore and the consumption of pork and pig products. The sequence similarity of the porcine strains to human strains was high, with the highest nucleotide identity (98.5%) reported here being similar to those reported in other countries like France (96.7%) (Colson et al, ) and Hong Kong (97.8%) (Chan et al, ). The association is further supported by our finding of disproportionate representation of HEV infections by ethnicity.…”
Section: Discussionsupporting
confidence: 85%
“…Although food‐borne infections in Asian cities have been mainly linked to genotype 4 (Chan et al, ; Jeong et al, ; Sridhar et al, ; Wibawa et al, ), except for China and Japan where genotypes 3 and 4 were both detected (Table ), we identified only one genotype 4 human case. Quite clearly, our study shows genotype 3a to be the main aetiological agent for most of the indigenous HEV cases in Singapore.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Blood sera gathered from sheep and sheep butchers in China showed 35.2% anti-HEV antibody in sheep blood, 57.7% in butcher's blood, and among sheep the most elevated cases were among adult in contrast with young ones and all the isolates belonged to genotype 4 52 . Study was done in HEV patients and different food items in Hong Kong and all HEV patients had 100% IgM anti-HEV and 82% of HEV RNA from pig liver, intestine and oysters 53 . Experts from Japan have shown the presence of HEV in wild boars in few territories and phylogenetic tree examination showed that the majority of the HEV strains resembled with genotype 3 54 .…”
Section: Integrated Disease Surveillance Programme (Idsp)mentioning
confidence: 99%
“…In this study, we investigated the association between addictive injection use and hepatitis E by conducting a matched cohort study among PWIDs and organ donors in Hong Kong, a HEV-A genotype 4 endemic area with a population HEV seroprevalence of 15.8% [ 25 , 26 ]. Both qualitative seroprevalence and HEV IgG concentrations were compared between groups.…”
Section: Introductionmentioning
confidence: 99%